A study on pragmatic equivalence in the English Vietnamese translation of the story Confession of an economic hit man" by John Perkins = Nghiên cứu tính tương đương ngữ dụng trong bản dịch Anh-Việt tác phẩm "Lời thú tội của một sát thủ kinh tế" của John P - Vũ, Thị Thanh Hoa (ĐHNN, 2017)
64 p. + CD-ROM